Polyurethane foams based on oligoetherols obtained from 6-aminouracil and alkylene carbonates - Chmiel-Szukiewicz, E. (Polimery, 2010)
The method of synthesis of polyurethane foams with good thermal stability, containing a 1,3-pyrimidine ring is presented. Oligoetherols obtained in reactions of 6-aminouracil (6-AU) with excess of ethylene carbonate (EC) and propylene carbonate (PC) were used as polyol substrates for synthesis of these foams. Properties of the foams, such as apparent density, water absorption, dimensional stability, thermal stability and compression strength were studied. The obtained foams show a good thermal stability up to 200 °C for a long time.